PENGEMBANGAN MEDIA AUDIO VISUAL BERBASIS SEJARAH LOKAL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN IPS SD DI KECAMATAN SINGOSARI KABUPATEN MALANG - Zahroh, Nur Lailatus (J-PAI: Jurnal Pendidikan Agama Islam, 2016)
This research aims to develop audio visual media that have been validated so that the media is suitable for using as a media representative in social studies learning in the school. The data in this research is gotten from questionnaire and obtained from the test subjects that include media expert, material expert and the students from 31 students of SDN Pagentan 03 Singosari. The result of the questionnaires are analyzed descriptively and qualitatively. According to media expert, the media is valid, so the media can be used in learning, but with revision. Matterial expert argue that the material is valid, so the media can be used.Material expert gives advice as a repair material for media excellence. Based on trial results to the 31 students who have tried this product, this media is interested and the material is understandably.Â Keywords: developtment, audio visual media, local history